2018
DOI: 10.1093/tropej/fmy012
|View full text |Cite
|
Sign up to set email alerts
|

An Open-label Randomized Controlled Trial to Compare Weight Gain of Very Low Birth Weight Babies with or without Addition of Coconut Oil to Breast Milk

Abstract: Oral supplementation of coconut oil along with breast milk did not increase growth parameters or result in change in body composition in very low birth weight (VLBW) babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
0
1
Order By: Relevance
“…Recently, Sumitha et al, conducted a randomized control trial on 60 babies to evaluate weight gain by using coconut oil as a breast milk fortifier. Contrary to findings of other studiesthey could not find significant increase in any of the growth parameters 20 .…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Sumitha et al, conducted a randomized control trial on 60 babies to evaluate weight gain by using coconut oil as a breast milk fortifier. Contrary to findings of other studiesthey could not find significant increase in any of the growth parameters 20 .…”
Section: Discussioncontrasting
confidence: 99%
“…The study finding is in line with a study conducted by Sumitha Arun, Manish Kumar, et al (2019) which reported that oral supplementation of virgin coconut oil (VCO) together with breast milk did not increase growth parameters or changes in body composition among very low birth weight babies, particularly in weight gain, triceps skinfold thickness, increase in head circumference and body fat percentage (Arun et al, 2019).…”
Section: Effectiveness Of Vco On Changes In Weight and Height Among U...supporting
confidence: 91%